Acute pancreatitis as a rare adverse event following COVID-19 vector-based vaccination: A case report - Nurgaliyeva, Bayan; Moldakaryzova, Aizhan; Khaidarov, Saken; Aldasheva, Zhannat (Acta Biomedica Atenei Parmensis, 2025)
Background: Acute pancreatitis (AP) has been reported rarely after vaccination against SARS‑CoV‑2. Case: We describe a 41‑year‑old vegetarian, non‑smoking male who developed AP five days after the first dose of the adenoviral vector vaccine Gam‑COVID‑Vac (Sputnik V). On admission serum amylase was 3600 U/L and abdominal ultrasound demonstrated an enlarged, oedematous pancreas without gall‑stones. The patient responded to conservative therapy and was discharged after seven days.Conclusion: Although causal inference cannot be drawn from a single observation, clinicians should remain aware of AP as a potential event after vector‑based COVID‑19 vaccination.